Social media marketing: a brand’s perspective; a case study of Hero MotoCorp Ltd. in Bangladesh - Ishaque, Soumiya Binte (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.